2021
DOI: 10.3389/fpubh.2021.679699
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Knowledge, Attitude and Practice of Personal Protection Among Different Types of Workers Returning to Work Under COVID-19 Epidemic

Abstract: Background: Since the outbreak of the coronavirus disease 2019 (COVID-19) world pandemic, it has had a significant negative impact on the economy and employment. The orderly resumption of work and production is an important factor in reducing the impact of the COVID-19 and an important guarantee of social and economic stability. The study aimed to investigate the knowledge, attitudes, and practice (KAP) of people returning to work about personal protection under the COVID-19 world pandemic.Methods: During Marc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
5
7
0
1
Order By: Relevance
“…With this in mind, it is possible that an overall high level of adherence to protective measures, such as 2 m distance in offices, signifies an overall level of distance which affects all workers. A study by Fan et al, which examined different types of workers, including public servants in the category of white-collar workers, demonstrated a high level of knowledge about protective measures and a high level of adherence among these workers [ 38 ], which agrees with our results. In other words, the lack of difference between workers who followed protective measures and those who did not may be explained by the very high overall adherence among municipal workers giving a protective effect to all workers whether they observed protective measures or not.…”
Section: Discussionsupporting
confidence: 91%
“…With this in mind, it is possible that an overall high level of adherence to protective measures, such as 2 m distance in offices, signifies an overall level of distance which affects all workers. A study by Fan et al, which examined different types of workers, including public servants in the category of white-collar workers, demonstrated a high level of knowledge about protective measures and a high level of adherence among these workers [ 38 ], which agrees with our results. In other words, the lack of difference between workers who followed protective measures and those who did not may be explained by the very high overall adherence among municipal workers giving a protective effect to all workers whether they observed protective measures or not.…”
Section: Discussionsupporting
confidence: 91%
“…The result was in line with the study conducted in Ethiopia which showed that the people working as a government officers and merchant were more likely to have sufficient knowledge on COVID-19 than those working as a laborer (47). Similar studies conducted in Turkey (35) and China (36) also illustrated the higher knowledge level on COVID-19 among the white-collar workers. The respondents having white-collar occupations mostly have easy access to information and strong learning ability further aids in increasing their attitude and practice.…”
Section: Discussionsupporting
confidence: 76%
“…The necessity of a high level of psychological readiness i.e., belief and acceptance towards the severity of disease particularly for behavioral change (30) increased the importance of the study. In addition, previous studies conducted on Ethiopia (31,32), Bangladesh (33,34), Turkey (35), China (36,37), Malaysia (38), Iran (39), Indonesia (40) and Cameroon (41) regarding knowledge, attitude and practice (KAP) on COVID-19 also provided substantiation of clear understanding of these concerns further underscored the significance of the study. However, there are limited studies regarding KAP on COVID-19 among general population in context of Nepal.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 55%
See 1 more Smart Citation
“…Hal ini sejalan dengan penelitian sebelumnya yang mengungkapkan bahwa terdapat pengaruh antara gender responden terhadap praktik penerapan perlindungan personal di saat COVID-19 menjadi epidemi. 18 Hasil penelitian ini sejalan dengan penelitian sebelumnya, di mana dari hasil pemodelan linier menunjukkan bahwa ada perbedaan signifikan kepatuhan terhadap prosedur perlindungan individu terhadap COVID-19 pada responden laki-laki dan perempuan. 5 Menurut asumsi peneliti, berdasarkan dari hasil penelitian sebelumnya, gender memiliki hubungan dengan kepatuhan terhadap rekomendasi perlindungan personal.…”
Section: Pembahasanunclassified